Effectiveness of strontium zinc phosphosilicate on the corrosion protection of AA2198-T851 aluminium alloy in sodium chloride solution. (December 2022) - Gad, Shedrack Musa; Emad, Seydgholamreza; Zhou, Xiaorong; Lyon, Stuart B.; Jin, Zelong; Dagwa, Ishaya Musa
Abstract: The effectiveness of strontium zinc phosphosilicate (SZP 391) as a corrosion inhibitor for the protection of Al–Cu–Li alloy in 0.5 M NaCl solution was evaluated using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarisation (PDP). The morphology of substrates were characterised with scanning and transmission electron microscopy (SEM) and (TEM). The corrosion rate of the substrates exposed to uninhibited solution increases with immersion time while those in inhibited solution showed significant reduction of corrosion rate. SEM and TEM revealed presence of film formed on the substrates' surface which serves as a barrier for blocking the access of aggressive ions. Highlights: Excellent correlation was established between electrochemical response and electron microscopy characterisation. The corrosion evolution of the substrate indicated that localised corrosion started in the vicinity of intermetallic particle. SZP 391 effectively inhibited the corrosion of AA2198–T851 alloy by preferential adsorption of inhibitive species at the intermetallic particle. Potentiodynamic polarisation response indicated a cathodic inhibition mechanism. The protective species confirmed by EDX spectra include Sr, Zn, P, and Si, which are the constituents of SZP 391 inhibitor.